Decadency of Nationalism Attitudes in The Community in The Kotabangon Village, Subdistrict Kotamobagu Timur - Julien Biringan,; Ferry Lourens Sampel Korompis,; Krifly Karaseran, (Technium Social Sciences Journal, 2023)
This research is expected to be able to distinguish and describe the frivolity of local patriotism in the Kotobangon area, the East Kotamobagu sub-region, the reasons for patriotism revelry, the attributes of patriotism, local in developing an attitude of respect for the Indonesian state. This study uses a traditional examination strategy where information is quantitative and investigations are subjective graphics, information sorting methods use perception, meetings and documentation, information examination is subjective. The consequence of this study shows that the recklessness of patriotism significantly affects the younger age both in terms of behavior and thinking. The community must play an active role because there are so many young people who do not reflect their love for the motherland and for Indonesia, for example, they do not use Indonesian properly and correctly, and like to use foreign goods. Therefore, the task of public authorities is very important to focus more on younger people, such as holding courses or social presentations, so as to broaden the character of patriotism.